Tissue microRNAs in non-small cell lung cancer detected with a new kind of liquid bead array detection system - Zheng, Yuan-Yuan (J Transl Med, 2020)
BACKGROUND: Commonly used miRNA detection methods cannot be applied for high-throughput analyses. However, this study was aimed to performed a liquid bead array detection system (LBAS) to detect tissue 6 miRNAs in non-small cell lung cancer (NSCLC). METHODS: In this study, evaluation of LBAS was performed to observe the precision, specificity, limitation and stability. Then, a total of 52 primary NSCLC patients who received resection operation without preoperative radiotherapy and chemotherapy between June 2013 and March 2014 were selected, and then the total RNA of the tissues were extracted. We prepared six NSCLC-related miRNAs for LBAS. After optimization and evaluation, LBAS was verified by detecting the relative expression levels of 6 microRNAs in the pathological tissues and corresponding normal tissues of 52 NSCLC patients. RESULTS: The results of evaluation of LBAS showed that the Mean Fluorescence Intensity (MFI) of the reaction only added with chimeric probes and beads showed no significant change after 180 days (P > 0.05). And the intra-assay Coefficient of Variation (CV) was between 1.57 and 3.5%, while the inter-assay CV was between 4.24 and 11.27%, indicating this system was ideal for diagnostic reagents. In addition, only the beads corresponding to the additional miRNAs showed high MFIs from 8426 to 18,769, whereas the fluorescence values of the other beads were under background levels (MFIs = 20 to 55) in each reaction, indicating no cross reactivity among the miRNAs. The limit of detection of miR-21, miR-210, miR-125b, miR-155, miR-375, and miR-31 were 5.27, 1.39, 1.85, 2.01, 1.34, and 2.73 amol/μL, respectively, showing that the lowest detection limit of miRNA by this system was under pM level. Then, the relative expression levels of miR-21, miR-210, miR-125b, miR-155, miR-375, and miR-31 by using this system were significantly correlated with NSCLC (P < 0.05). And the results of AUC method indicated that specific of the LBAS system was 94.2%. CONCLUSIONS: Our findings suggest that LBAS was simple, high-throughput, and freely combined with absolute quantification. Thus, this system could be applied for tumor miRNAs detection.